Fluorescent probes for “off–on” sensitive and selective detection of mercury ions and l -cysteine based on graphitic carbon nitride nanosheets - Zhang, Hanqiang; Huang, Yihong; Hu, Shirong; Huang, Qitong; Wei, Chan; Zhang, Wuxiang; Kang, Lianping; Huang, Zhouyi; Hao, Aiyou (Journal of materials chemistry. C, Materials for optical and electronic devices, 2015)
A novel approach for preparation of graphitic carbon nitride nanosheets (CNNS) from stripping graphitic carbon nitride by strong acid and ultrasonic technology was demonstrated in this study for the first time. Transmission electron microscopy (TEM) was employed to characterize the surface morphology. Atomic force microscope (AFM) was carried out to characterize the thickness of nanosheets. X-Ray diffraction (XRD) was performed to estimate the lattice structure. X-Ray photoelectron spectroscopy (XPS) was carried out to characterize the surface composition and element analysis. Fourier transform infrared spectroscopy (FT-IR) was allowed to identify the functional groups. The as-synthesized CNNS exhibited excellent emission property as well as excitation-independent emission behavior, and fluorescence quantum yields could reach approximately 12.53%. Mercury ion (Hg 2+ ) can make a result of quenching the significant intensity of fluorescence of CNNS by formation of a covalent bond between empty orbital of Hg 2+ and the π electrons of N (turn-off). Moreover, the addition of the l -cysteine ( l -Cys) can enhance the intensity of fluorescence of the CNNS– Hg 2+ system through the thiol group of l -Cys anchored with Hg 2+ and drag it from the surface of CNNS (turn-on). The CNNS was consequently functioned as a fluorescence probe towards “off–on” detection of Hg 2+ and l -Cys with high sensitivity and selectivity. Moreover, the fluorescent probe was applied to detect tap water and well water with satisfactory results.